EVALUATING THE LEVEL AND CHOOSING A DIGITALIZATION STRATEGY HIGHER EDUCATIONAL INSTITUTION - Glukhov Vladimir; Byankin Anton; Burdakova Galina; Babkin Ivan (Научно-технические ведомости СПбГПУ: Экономические науки, 2021)
The active development and application of digital tools and technologies in the economy determines the need to implement strategies for digital transformation of various economic entities. Higher education institutions are no exception, which are open socio-economic systems that are significantly affected by the processes of digitalization in society. Digital changes taking place in the market of educational services are radically changing approaches to the implementation of the educational process, thereby causing the need to review strategic objectives and establish priority areas for digital development. The relevance of determining the level of digital development of an educational institution is due to the need to develop strategic directions for digitalization of its activities in order to increase competitiveness. Universities that want to take a strong position in the educational services market should develop and implement appropriate strategic and tactical measures in the field of digitalization in a timely manner. The choice of digital transformation strategies should be based, inter alia, on determining the current level of digitalization and analyzing key factors in the internal environment of universities. When choosing a strategy, the determining factors are financial resources, technical and technological base, and competence in the field of digitalization. The purpose of the study is to develop recommendations for assessing the level of digitalization of educational activities of higher education institutions and the possible choice of digital transformation strategies based on it. The authors reviewed the experience and formalized the main directions of strategic development of universities in the field of digitalization of educational activities related to the use of educational programs in various educational services markets. The relationship between the level of digitalization of the University and the strategy of digital transformation is substantiated. The key factors and components of the internal environment that determine the choice of strategies for the development of universities are identified. The main indicators of evaluation and monitoring are summarized, allowing both to assess the level of digitalization of the University's activities, and to choose a specific strategy and tactics for digital transformation. The research results and recommendations developed on their basis can be used in the practice of developing and implementing strategies for digitalization of the educational process in higher education institutions.